Clinical Significance of Inflammatory Biomarkers in Acute Pediatric Diarrhea - Park, Yoonseon (Pediatr Gastroenterol Hepatol Nutr, 2019)
PURPOSE: The aim of this study was to evaluate the clinical significance of inflammatory biomarkers in acute infectious diarrhea among children. METHODS: Clinical parameters including fever, bacterial and viral etiology based on stool culture and multiplex polymerase chain reaction, and nine biomarkers including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) and leukocytes in blood and calprotectin, lactoferrin, myeloperoxidase, polymorphonuclear elastase, leukocytes, and occult blood in feces were evaluated in children who were hospitalized due to acute diarrhea without underlying disease. RESULTS: A total of 62 patients were included. Among these patients, 33 had fever, 18 showed bacterial infections, and 40 patients were infected with 43 viruses. Of all the biomarkers, CRP was significantly correlated with fever (p<0.001). CRP, ESR, calprotectin, lactoferrin, myeloperoxidase, fecal leukocytes, and occult blood were significantly associated with infection with bacterial pathogens (p<0.001, p=0.04, p=0.03, p=0.003, p=0.02, p=0.03, p=0.002, respectively). The combination of CRP and fecal lactoferrin at their best cut-off values (13.7 mg/L and 22.8 µg/mL, respectively) yielded a sensitivity of 72.2%, and a specificity of 95.5% for bacterial etiology compared with their individual use. CONCLUSION: Blood CRP is a useful diagnostic marker for both fever and bacterial etiology in acute pediatric diarrhea. The combination of CRP and fecal lactoferrin yields better diagnostic capability for bacterial etiology than their use alone for acute diarrhea in children without underlying gastrointestinal disease.